BILATERAL FOCAL XANTHOGRANULOMATOUS PYELONEPHRITIS : A CASE REPORT AND LITERATURE REVIEW - LIKKASIT, Wipaporn; ANANTRASIRICHAP, Wannee (The ASEAN Journal of Radiology, 2023)
Xanthogranulomatous pyelonephritis (XPN or XGP ) is an uncommon entity. mostly unilateral. A case of bilateral focal xanthogranulomatous pyelonephritis is reported with literatures reviewed. Accurate preoperative diagnosis is difficult : however ultrasound and CT may give the suggestion of this disease.